1988
DOI: 10.1021/jo00244a002
|View full text |Cite
|
Sign up to set email alerts
|

Type I intramolecular cycloadditions of vinylketenes

Abstract: NMR (CDC13, 250 MHz) d 2.66 ( 8 , 3 H), 7.2-8.0 (m, 10 H), 8.98 (d, J = 8 Hz, 2 H), 9.96 (s, 1 H).Pentaphen-5-01 Acetate (25). This compound was prepared from 0.75 g of 13a in the same manner as 24 except that the reaction with DMAD was carried out for 8 days. Small amounts of TCAA were added daily after 4 days. To the final reaction mixture was added 150 mL of water. The resulting precipitate was filtered, air-dried, and chromatographed on silica gel, eluting with toluene. Removal of the solvent from the appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…Two-dimensional NMR spectroscopy indicated that the major diastereomer formed in all cases possesses the 2,3- syn , 2,5- syn stereochemistry (cf. 34a ), in accord with literature precedent for similar ketene–olefin cycloadditions. It is likely that a substrate conformer in which the C5 group adopts a pseudoequatorial orientation in the transition state for [2 + 2] cycloaddition gives rise to the observed stereochemistry.…”
Section: Thermal Retro-ene/[2 + 2] Cycloaddition Reactions Of Tert-bu...supporting
confidence: 82%
See 1 more Smart Citation
“…Two-dimensional NMR spectroscopy indicated that the major diastereomer formed in all cases possesses the 2,3- syn , 2,5- syn stereochemistry (cf. 34a ), in accord with literature precedent for similar ketene–olefin cycloadditions. It is likely that a substrate conformer in which the C5 group adopts a pseudoequatorial orientation in the transition state for [2 + 2] cycloaddition gives rise to the observed stereochemistry.…”
Section: Thermal Retro-ene/[2 + 2] Cycloaddition Reactions Of Tert-bu...supporting
confidence: 82%
“…Ketene intermediates are commonplace in the sigmatropic rearrangement chemistry of allyl and benzyl alkynyl ethers. It has been shown that ketenes also undergo a facile [2 + 2] cycloaddition with alkenes to form cyclobutanones, and the intramolecular variant of this process has been studied extensively by the groups of Marko, Snider, and Brady . However, the ketene intermediates utilized for these [2 + 2] cycloaddition reactions are most frequently generated from the corresponding acid chlorides by treatment with tertiary amines.…”
Section: Thermal Retro-ene/[2 + 2] Cycloaddition Reactions Of Tert-bu...mentioning
confidence: 99%
“…Analytical data agreed with those reported in the literature. [28] Methyl 2-[tert-butoxycarbonyl(3-methylpent-4-enyl)amino]acrylate (17): This compound was synthesized from 5 and 15, following general procedure B; colorless oil; yield: 553 mg (77 %). (18): This compound was synthesized from 5 and 16, following general procedure B; colorless oil; yield: 281 mg (64 %).…”
Section: -Iodo-3-methylpent-1-ene (15)mentioning
confidence: 99%
“…Work-up after this step was carried out by pouring the mixture into a cold HCl solution, separating the organic phase, extracting the aqueous phase with Et 2 O and concentrating the combined organic phases; colorless liquid; yield of 26: 205 mg (48 % over 2 steps). (27) General Procedure E for Ring-Closing Metathesis of 8, [28][29][30] A solution of the substrate in toluene (~3 mm) was stirred under an inert atmosphere at 80 8C. Catalyst A (5 mol %) was added and the reaction mixtuire was stirred at 80 8C for 1 h. Next, a second portion of A (5 mol %) was added and the reaction mixture was stirred overnight at 80 8C.…”
Section: General Procedures D For the Transformation Of Ethyl Esters Imentioning
confidence: 99%
See 1 more Smart Citation